A PERVERSA CONCENTRAÇÃO DE RENDA VIA SISTEMA TRIBUTÁRIO - Flávia Rebecca Fernandes Rocha; Epitácio Macário (Revista de Políticas Públicas, 2014)
The Brazilian state has a significant tax revenues based primarily on taxes on the consumption of goods and services. Thus, the article shows, that it makes it regressive and unfair to encompass rich and poor in the same propor tions, while the taxation of speculative capital and assets that could intervene heavily in the distribution of income does not exist or is very shy . Also highlights that, in mediated form, the tax burden of a country reflects the correlation of class forces in dispute and, in Brazil, has strengthened and propelled the perverse concentration of national income, which allied efforts to train primary surplus results in damage to budget funding for implementation and funding of public policies. At last, it sho ws that, the double punishment falls on the working classes is the payment of excise taxes is the absence of public po licies to match the needs of a society riven by inequality.